Longitudinal Study of the Relationship Between Conscious Self-Regulation, School Engagement and Student Academic Achievement - Fomina T.G; Filippova E.V; Morosanova V.I (Moscow State University of Psychology and Education, 2021)
The study seeks to examine the longitudinal relationship between school en¬gagement, conscious self-regulation, and student academic achievement. Research analysis covers the data obtained in two longitudinal studies of two student groups: 8-9 graders (N=106) and 10-11 graders (N=96). Diagnostics of self-regulation was carried out by means of "Self-Regulation Profile of Learn¬ing Activity Questionnaire - SRPLAQ", school engagement was assessed using "A Multidimensional School Engagement Scale» (Wang et al., 2019; Fomina, Mo¬rosanova, 2020). The average value of annual marks in core academic subjects served as an indicator of academic achievement. The measurements were taken twice, with one-year interval. The study revealed significant changes (decrease) in the level of students' school engagement during their transition from grade 8 to grade 9. When moving from grade 10 to grade 11, the students significantly increase their levels of self-regulation, school engagement, and academic perfor¬mance. Cross-lagged panel analysis made it possible to establish that conscious self-regulation is a significant predictor of successful learning and high student engagement during the transition to the 9th grade. Whereas in grade 11, student engagement in the educational process, as well as previous academic success, plays a more significant role for successful learning. The data obtained allowed for specifying the directions of the causal relationship between school engage¬ment, conscious self-regulation, and academic achievement of students in differ¬ent periods of schooling.